Crime witness accounts - Weiss, Karen G. (Theoretical criminology, 2021)
Contrary to the social expectation that good citizens should help others in need, persons who witness crime do not always intervene to help, or see it as their responsibility to do so. This study explores the reasons why witnesses choose not to call police or help in other ways by elucidating the accounts that nonintervening witnesses use to convince others and themselves that intervention was not necessary or appropriate. Drawing from open-ended survey responses, five neutralizing accounts are identified, two that deny the intervenability of crime (by denying harm or blaming victims), and three that deny responsibility to help (by denying capability, asserting risk, or rejecting a guardianship role). Identifying the accounts that normalize crime and make it easier for witnesses to “do nothing” contributes to a more nuanced understanding of witness decision making and nonintervening responses that, in turn, can contribute to the persistence of crime.